Ferulic acid uptake by soybean root in nutrient culture - Lucio Ferrarese, Maria de Lourdes; Ferrarese-Filho, Osvaldo; Rodrigues, Joǎo Domingos [UNESP] (Springer Nature, 2000)
Ferulic acid uptake by soybean root in nutrient culture was investigated by the depletion method at different concentrations, temperatures and pH. Results showed that soybean roots absorbed this compound at greater rates in the concentrations between 0.05-mM and 1.0-mM and it was concentration dependent. Ferulic acid uptake was unaffected at pH 4.5 or 6.0 but reduced at pH 7.0. At pH 6.0, uptake rates decreased significantly with increasing temperature of nutrient solution.
Keywords: Absorption; Ferulic acid; Glycine max L. Merr.; pH; Roots; Temperature